Association of genotypes by polymorphic variant C-108T of PON1 gene with the risk of developing breast cancer and hypertensive disease in women - Fishchuk, L.Ye. (Вiopolymers and Cell, 2014)
Aim. To analyze the effect of the polymorphic variant C-108T of PON1 gene on the risk of developing breast cancer (BC) and hypertensive disease (HD) in women. Methods. 130 women with non-complicated HD of degree II and 131 women with BC of I and II stages without cardiovascular complications were enrolled in the study. The control group was composed of 102 women without cardiovascular and oncological pathologies. Molecular-genetic analysis was performed on DNA isolated from the samples of peripheral blood. Genotyping of polymorphic variant C-108T of PON1 gene was carried out with the use of PCR-RFLP method. Results. It has been revealed that the presence of -108CC genotype of PON1 gene in women elevates the risk of HD development in more than 1.5 times. As for women over 54, the presence of -108CC genotype of PON1 gene is associated with a decreased risk of BC by almost 4 times and, in contrary, the presence of -108CT genotype of PON1 gene is associated with an increased risk of BC by more than 3 times. Conclusions. Polymorphic variant C-108T of PON1 gene may be considered as possible prognostic marker of BC and HD development in women.